PEMBUATAN WEBSITE SUNVERA SEBAGAI MEDIA PROMOSI KOTA PONTIANAK - Hariansyah; Sujatmiko, Wandi; Arianti, Tia; Adriansyah , Herry (Sustainable, 2023)
The website is part of the use of internet technology. Where all the data on the website is stored at an internet address. So when the user or users will access, must know the url address of the web Research Objectives: The general purpose that can be explained from this research is to know how to create a Sunvera Promotional Website. Research results: The results of this study can be used to help improve the knowledge and skills of students and employees of CV Sunvera in using the Sunvera Promotion Website. Conclusion This study only discusses from design to product development, namely the making of learning media applications so that it can facilitate practicum for midwifery students. using the Research and Development method, so that the result is in the form of application development, namely the creation of new products. In the results of this study there are still many shortcomings, therefore improvements will be made in further research.